THE MARKETING OF FRESHWATER FISH IN THE MARKET TERATAK BULUH, SIAK HULU DISTRICT KAMPAR REGENCY RIAU PROVINCE - Sukemi '; Hendrik '; Ridar Hendri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This reseach is about marketing of freshwater fish in the Market Teratak Buluh and held on 25 February to 15 March 2016 in the Market Teratak Buluh Siak Hulu District Kampar Regency Riau Province. The purpose of this study was to analyze the supply and demand for freshwater fish and to determine the marketing channels of freshwater fish in the Market Teratak Buluh. The method used in this study is a survey method.The results of this study indicate that the supply of freshwater fish that exist in the market Teratak Buluh during average season amounted to 6.145 kg/day, while in the absence of an average season amounted to 2,830 kg/day, and the fish come from various areas such as Palalawan, Siak, Rokan Hulu, Kampar, Palembang and Medan. The demand for freshwater fish during average season amounted to 6.145 kg/day, while in the absence of an average season amounted to 2.830 kg/day and fish demand comes from the city of Pekanbaru, Kampar, Kuantan Singingi, and Palembang. This study marketing channels starting from fishermen to traders from each region, then the fish brought to Market of Teratak Buluh and fish is entrusted to the agent who has a stall in the Market Teratak Buluh. Furthermore Agents sell freshwater fish to traders who come directly to the retailer Market of Teratak Buluh then sold in various markets in the city of Pekanbaru.Keywords: Supply, Demand, Channel Marketing, Trader Gatherer, Agents, Retailers Saler